Religiosity and Entrepreneurial Intention: A Study of Strawberry Generation - Soelaiman, Lydiawati; Saktiana, Galuh Mira (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2024)
This research will be conducted on the Strawberry Generation, better known as Generation Z, aimed at testing religiosity on entrepreneurial intentions mediated by self-efficacy, subjective norms, attitudes, and entrepreneurial motivation. This study uses a non-probability sampling technique with a purposive sampling method, with a sample size of 207 respondents. The analysis tool that will be used is SEM AMOS 22. The influence of self-efficacy, subjective norms, and entrepreneurial attitudes as a mediation of the relationship between religiosity and the intensity of entrepreneurship in Generation Z is significant, meaning that someone religious makes Generation Z have the intention to entrepreneur because it has high self-efficacy, subjective norms and also high entrepreneurial attitudes. Entrepreneurial motivation apparently does not make a religious entrepreneur intend to have an entrepreneur for Generation Z.